Comprehensive Analysis of the Implication of PGRMC1 in Triple-Negative Breast Cancer - Xu, Xin; Ruan, Xiangyan; Zhang, Ying; Cai, Guiju; Ju, Rui; Yang, Yu; Cheng, Jiaojiao; Gu, Muqing (Frontiers in Bioengineering and Biotechnology, 2021)
TNBC represents the most malignant subtype of breast cancer with heterogenicity and poor prognosis. PGRMC1 has been reported to predict worse prognosis and correlate with MHT mediated signal transduction in breast cancer, whereas its involvement in TNBC remains poorly explored. The purpose of the study was to explore the roles of PGRMC1 in TNBC. Bioinformatic approaches were performed to analyzed the expression of PGRMC1 among different subtypes of breast cancers using RNA-seq data from the TCGA, METABRIC and GEO databases. PGRMC1 mRNA expression and survival in breast cancer were analyzed. Furthermore, we analyzed the expression of PGRMC1 in TNBC by single cell RNA-seq data and immunohistochemistry. The expression of PGRMC1 in TNBC group was significantly higher compared with that of Luminal subtypes, especially in the epithelia cells, which was further proved by IHC at protein level. Better overall survival (p = 0.027) was observed in the patients with lower expression of PGRMC1. Different states of hormone and Her2 receptors contributed to the distinct functions of PGRMC1. In TNBC, PGRMC1 might play an important role in mitochondrial functions. In summary, this study revealed the correlation between PGRMC1 expression and its clinical significance in TNBC, probably through mitochondria-associated pathway, which may provide new ideas for prognosis and therapy of TNBC.